Central diabetes insipidus and burn trauma. (October 2022) - Kopel, Jonathan; Moreno, Tanir; Singh, Simran; Van-Spronsen, Nicole; Sorensen, Grant; Griswold, John
Diabetes insipidus (DI) is characterized by polyuria and polydipsia. In most cases, the condition results from either an inadequate release or resistance to the activity of antidiuretic hormone in the renal collecting tubules. The underlying pathophysiology may be related to destruction the destruction or degeneration of neurons from inflammatory, autoimmune diseases, vascular diseases, Langerhans cell histiocytosis, sarcoidosis, or trauma. However, a large majority of diabetes insipidus cases (50%) are considered idiopathic. An exceedingly rare cause of idiopathic central DI occurs in burn injuries, which has only been reported in eight cases. We present an extremely rare case of idiopathic DI in a 15-year-old male with 76% total body surface area (TBSA) burns with the development of idiopathic central DI. An extensive literature review was accomplished to compare this case with the small number of previously reported case reports of idiopathic DI in burn patients. Lay Summary: Diabetes insipidus (DI) is a rare complication of burn injuries that results from the destruction of neurons involved in the secretion of antidiuretic hormone from the pituitary gland. Only eight cases of DI have been reported in the literature in association to burn injuries. The patient in this case report received immediate fluid resuscitation, burn treatment, and intensive observation after the initial burn injury. The rapid response was likely the main reason for the absence of neurological damage as reported in the CT image. Therefore, the treatment of burn injuries remains an important step for reducing neurological damage and hormonal dysregulation leading to diabetes insipidus.